Tannin tolerance lactic acid bacteria screening and their effects on fermentation quality of stylo and soybean silages - Gao, Lin; Guo, Xiang; Wu, Shuo; Chen, Dandan; Ge, Liangfa; Zhou, Wei; Zhang, Qing; Pian, Ruiqi (Frontiers in Microbiology, 2022)
Some excellent legume forages are difficult to ensile naturally due to their high buffering capacity and low water-soluble carbohydrate content. This may cause serious problems like proteolysis. In the present study, strains of lactic acid bacteria with high acid productivity and high tannin tolerance were screened from different silages and combined with tannic acid (TA) as an addition to ensiling. The screened strains were identified as Lactobacillus plantarum (LP), with four of these strains then selected for their high tannin tolerance. Stylosanthes guianensis and whole-plant soybean were ensiled with 1% and 2% (fresh matter basis) TA, four LP strains alone (6 log10 colony forming units per gram of fresh matter), or TA combined with LP strains. Fermentation parameters and in vitro rumen fermentation characteristics were analyzed after 30 days of fermentation. The results showed that TA + LP can be used to reduce pH values (P < 0.01), nonprotein nitrogen (P < 0.01), and ammonia-nitrogen (P < 0.01). The in vitro crude protein digestibility of whole-plant soybean silage was also decreased with the addition of TA + LP (P < 0.01). These results indicate that the addition of TA combined with tannin tolerance LP strains may improve the fermentation quality of legume silage, especially for reducing proteolysis.